Effects of extracellular calcium and surgical techniques on restoration of axonal continuity by polyethylene glycol fusion following complete cut or crush severance of rat sciatic nerves. Issue 3 (5th January 2016) - Ghergherehchi, Cameron L.; Bittner, George D.; Hastings, Robert Louis; Mikesh, Michelle; Riley, D. Colton; Trevino, Richard C.; Schallert, Tim; Thayer, Wesley P.; Bhupanapadu Sunkesula, Solomon Raju; Ha, Tu‐Anh N.; Munoz, Nicolas; Pyarali, Monika; et al.
Abstract : Complete crush or cut severance of sciatic nerve axons in rats and other mammals produces immediate loss of axonal continuity. Loss of locomotor functions subserved by those axons is restored only after months, if ever, by outgrowths regenerating at ∼1 mm/day from the proximal stumps of severed axonal segments. The distal stump of a severed axon typically begins to degenerate in 1–3 days. We recently developed a polyethylene glycol (PEG) fusion technology, consisting of sequential exposure of severed axonal ends to hypotonic Ca 2+ ‐free saline, methylene blue, PEG in distilled water, and finally Ca 2+ ‐containing isotonic saline. This study examines factors that affect the PEG fusion restoration of axonal continuity within minutes, as measured by conduction of action potentials and diffusion of an intracellular fluorescent dye across the lesion site of rat sciatic nerves completely cut or crush severed in the midthigh. Also examined are factors that affect the longer‐term PEG fusion restoration of lost behavioral functions within days to weeks, as measured by the sciatic functional index. We report that exposure of cut‐severed axonal ends to Ca 2+ ‐containing saline prior to PEG fusion and stretch/tension of proximal or distal axonal segments of cut‐severed axons decrease PEG fusion success. Conversely, trimming cut‐severed ends in Ca 2+ ‐free saline just prior to PEG fusion increases PEG fusion success. PEG fusion prevents or retards the Wallerian degeneration of cut‐severed axons, as assessed by measures of axon diameter and G ratio. PEG fusion may produce a paradigm shift in the treatment of peripheral nerve injuries. © 2016 Wiley Periodicals, Inc. Abstract : Distal portions of cut‐severed sciatic nerves that are repaired with microsutures and PEG fusion have larger diameters compared with sciatic nerves repaired with microsutures. That is, PEG fusion prevents or slows Wallerian degeneration of cut‐severed axons.